THE PROBLEM OF THE EMERGENCE OF THE KYRGYZ LITERARY LANGUAGE IN THE STUDY OF ACADEMICIAN S. ZH. MUSAEV - Abdykerimova A. E.; Ryskeldi kyzy A. (Vestnik Issyk-Kulʹskogo universiteta, 2025)
The article is devoted to a brief analysis of the issue of the emergence and development of the Kyrgyz literary language in the study of the famous Kyrgyz linguist, academician S. Zh. Musaev. It is known that for many years the prevailing opinion was that the Kyrgyz literary language arose and developed only after the October Revolution, under the influence of the creation of writing and printing. At the same time, firstly, there is a deep misunderstanding of the genesis and history of the problem of the literary language as a whole, secondly, the mechanical application of theories and provisions based on materials from other languages to the Kyrgyz language, thirdly, there is a limited opinion that the literary language should exist and exists only in written form, fourth, the ideological demands that existed at that time played a role. Systematic research and analysis of this issue by S. J. Musaev proved that the national Kyrgyz language for many centuries had a developed, naturally normalized, polyvalent, multifunctional, polysemantic subsystem of the oral literary language, processed on the basis of the principle of selection of linguistic means.